Analisis Kapasitas Belly Cargo pada Penerbangan Berjadwal Domestik Indonesia - Mufti Arifin (FTK UNSURYA, 2016)
Domestic air cargo using narrow body passenger (pax) aircraft belly has limited capacity as remaining from maximum payload minus pax payload. The ratio of revenue cargo and revenue pax from schedule domestic airlines production data from 2004-2014 rely at 9 kg/pax and highest at 14 kg/pax. This study compares belly cargo capacity from ten aircraft types that operates in Indonesia’s domestic route to air cargo demand estimation based on ratio data. All types at load factor 0.8 have belly cargo capacity larger than demand estimation. At full pax condition, ATR42-500, ATR72-500, ATR72-600, B737-300, B737-800, B737-900ER, and CRJ1000 still have belly cargo capacity larger than demand estimation. Smaller belly cargo capacity than demand only at A320, B737-400, and B737-500 with ratio 14 kg/pax, and only at A320 with ratio 9 kg/pax.